Advancements in Biodegradable Materials: Impacts on Soil and Water Quality - Singh, Hanumant (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
This study explores the degradation rates of various biodegradable materials and their impact on soil and water quality under both laboratory and field conditions. The materials examined include polylactic acid (PLA), polyhydroxyalkanoates (PHA), starch-based plastics, cellulose-based films, and compostable plastics. Results show significant variation in degradation rates, with cellulose-based films and starch-based plastics exhibiting the fastest degradation, while PLA degraded the slowest, particularly in aquatic environments. In soil, the degradation of biodegradable materials led to increased microbial activity and changes in nutrient levels, particularly nitrogen and phosphorus. However, concerns about nutrient pollution and soil imbalances emerged, particularly with the faster-degrading materials. In aquatic environments, the impact of biodegradable materials on water quality was less pronounced, with only slight changes in dissolved oxygen, nitrate, and phosphate levels. The study emphasizes the need for careful management and monitoring of biodegradable materials to prevent unintended environmental consequences, such as nutrient pollution or microbial imbalances. These findings contribute to the growing understanding of biodegradable materials' real-world performance and their potential to serve as a more sustainable alternative to conventional plastics, while also highlighting the challenges associated with their environmental impact.